2022
DOI: 10.14740/jem819
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Dyslipidemia in Obese Young Adult Subjects as Measured by Various Obesity Indices

Abstract: Background: Obesity is strongly associated with atherogenic dyslipidemia phenotype and is an independent risk factor of cardiovascular disease (CVD). Besides body mass index (BMI), there are various obesity indices, namely waist circumference (WC) to detect central obesity, and percentage of body fat (%BF) using bioimpedance analysis (BIA) to detect peripheral-central obesity. The aim of this study is to determine which obesity index is better in predicting dyslipidemia. Methods:This cross-sectional study invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The control group in the DZ population demonstrates a higher BMI, compared with the MZ population, along with higher levels of VLDL metabolites in the DZ control group and higher levels of HDL in the MZ control group. This is in line with previous reports on dyslipidemia and obesity 70 , 71 . To cope with this issue, future work should envision individual reference intervals, that exploit longitudinal subject-specific data rather than looking into population ranges 72 .…”
Section: Discussionsupporting
confidence: 94%
“…The control group in the DZ population demonstrates a higher BMI, compared with the MZ population, along with higher levels of VLDL metabolites in the DZ control group and higher levels of HDL in the MZ control group. This is in line with previous reports on dyslipidemia and obesity 70 , 71 . To cope with this issue, future work should envision individual reference intervals, that exploit longitudinal subject-specific data rather than looking into population ranges 72 .…”
Section: Discussionsupporting
confidence: 94%
“…This relationship remained signi cant after adjusting for age and gender variables. Our nding is consistent with Yudin et al study (12). Various studies also reported that obesity contributes to the release of large amounts of free fatty acids by lipolysis, which leads to dyslipidemia (22,23).…”
Section: Discussionsupporting
confidence: 93%
“…Abnormalities in lipid pro le in obese patients include elevation in triglyceride (TG), very low-density lipoprotein (VLDL), apolipoprotein B (Apo B), nonhigh-density lipoprotein cholesterol (non-HDL), small dense low-density lipoprotein (sdLDL), low-density lipoprotein (LDL) levels, but decreasing in HDL and Apo A1 (10,11). Visceral adipose tissue (VAT), which is mainly increased in obese individuals, causes elevated TG, sdLDL, and low HDL; also, the accumulation of excess fat in the abdomen is the main cause of insulin resistance, which both are related to the development of atherosclerosis and signi cantly in uences coronary artery disease (12).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Yudin R et al concluded that Obesity based on BMI is related to HDL-C and TG when they observed the lower concentration of HDL-C and higher concentration of TG in obese patients similar to this study. 24 The pathophysiology behind Obesity is multifactorial, including hepatic overproduction of VLDL, decreased circulating TG lipolysis and impaired peripheral FFA trapping, increased FFA fluxes from adipocytes to the liver and other tissues, and the formation of small dense LDL in the case group compared to the control group in this study. 25 Ranganathan S, et al concurred with these findings, stating that people with high BMI had a higher risk of dyslipidaemia than those with normal BMI.…”
Section: Discussionmentioning
confidence: 67%